2015
DOI: 10.1021/jp510179p
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Dependent Transport and Optical Properties of Transparent Half-Metallic g-C4N3 Films

Abstract: Half-metallic materials play an essential role in the spin-dependent transport study, and so far it is believed that the 3d transitional metal elements are necessary to obtain a ferromagnetic state. Herein, we demonstrate that the metal free two-dimensional graphitic carbon nitride (g-C4N3) film show half metallic state and this is independent of the film thickness and stacking order. We find that the half-metallicity results in a very large magnetoresistance even at finite bias. Moreover, we have also investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…We performed electron transport calculations by means of the NEGF extension of the OpenMX code, 29 which is by now widely used. [38][39][40][41][42][43] The model implemented in this software makes use of periodic boundary conditions. The basis sets employed consist of linear combinations of atomic orbitals generated by a confinement scheme which yields wave functions with zero value beyond a chosen cutoff radius.…”
Section: Methodsmentioning
confidence: 99%
“…We performed electron transport calculations by means of the NEGF extension of the OpenMX code, 29 which is by now widely used. [38][39][40][41][42][43] The model implemented in this software makes use of periodic boundary conditions. The basis sets employed consist of linear combinations of atomic orbitals generated by a confinement scheme which yields wave functions with zero value beyond a chosen cutoff radius.…”
Section: Methodsmentioning
confidence: 99%
“…Two-dimensional (2D) materials have a very large volume to surface ratio, so they display remarkable physical, chemical, mechanical and electrical properties. Owing to these properties, graphene, BN, C 4 N 3 and MoS 2 are receiving extensive research interest due to their unique physical properties for innovative potential device applications 1 2 3 4 5 6 7 8 . Very recently, a new 2D material phosphorene named after its parent black phosphorous was mechanically exfoliated by scotch tape based microcleavage method from a layered bulk black phosphorus and also a single layer phosphorene was obtained by plasma-assisted fabrication process 9 10 .…”
mentioning
confidence: 99%
“…It has been proposed that the C and N connectivity forms interconnecting molecular islands of melem units on the 2D graphite‐like sheets leaving triangular gaps in between these triangular melem units (a‐b plane) . Repetitive stacking of these layers in AAA or ABA pattern aligns these gaps thereby generating long range channels in the c‐direction perpendicular to the (a‐b) plane of g‐C 3 N 4 sheets . Theoretical as well as experimental studies have already shown that both charged (i. e. ions) and uncharged species (molecule, quantum dots) can suitably reside in these pores.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Repetitive stacking of these layers in AAA or ABA pattern aligns these gaps thereby generating long range channels in the c-direction perpendicular to the (a-b) plane of g-C 3 N 4 sheets. [24] Theoretical as well as experimental studies have already shown that both charged (i. e. ions [25] ) and uncharged species (molecule, [26] quantum dots [21] ) can suitably reside in these pores. Extensive research has shown that it is even possible to map the exact location of the cations and anions in such pockets.…”
Section: Introductionmentioning
confidence: 99%